VITKA - KATERINA TUCKOVA'S DRAMA DEBUT - Lollok, Marek (Bohemica Olomucensia, 2020)
The paper Vitka - Katerina Tuckova's drama debut deals with the theatre play Vitka by one of the most successful young Czech novelists Katerina Tuckova. The main character of this play is inspired by the Czech music composer and conductor Vitezslava Kapralova (1915-1940) who died tragically at the age of twenty five years. This paper analyzes some of the main features of Tuckova's play and, besides other things, particularly focuses on the strategies and means of language supporting the authenticity impression. It also considers a broader theatre and dramatical context as well as resources that Katerina Tuckova exploated as a basis for her text.
Keywords: contemporary Czech theatre; drama; Vitezslava Kapralova; Katerina Tuckova